Intimal sarcomas and undifferentiated cardiac sarcomas carry mutually exclusive MDM2, MDM4, and CDK6 amplifications and share a common DNA methylation signature - Kölsche, Christian; Benhamida, Jamal K.; Kommoss, Felix; Stichel, Damian; Jones, David T. W.; Pfister, Stefan; Heilig, Christoph E.; Fröhling, Stefan; Stenzinger, Albrecht; Buslei, Rolf; Mentzel, Thomas; Baumhoer, Daniel; et al. (Modern pathology, 2021)
Undifferentiated mesenchymal tumors arising from the inner lining (intima) of large arteries are classified as intimal sarcomas (ISA) with MDM2 amplification as their molecular hallmark. Interestingly, undifferentiated pleomorphic sarcomas (UPS) of the heart have recently been suggested to represent the cardiac analog of ISA due to morphological overlap and high prevalence of MDM2 amplifications in both neoplasms. However, little is known about ISAs and cardiac UPS without MDM2 amplifications and molecular data supporting their common classification is sparse. Here, we report a series of 35 cases comprising 25 ISAs of the pulmonary artery, one ISA of the renal artery and 9 UPS of the left atrium. Tumors were analyzed utilizing the Illumina Infinium MethylationEPIC BeadChip array, enabling copy number profile generation and unsupervised DNA methylation analysis. DNA methylation patterns were investigated using t-distributed stochastic neighbor embedding (t-SNE) analysis. Histologically, all ISAs and UPS of the left atrium resembled extra-cardiac UPS. All cases exhibited highly complex karyotypes with overlapping patterns between ISA and UPS. 29/35 cases showed mutually exclusive amplifications in the cell-cycle associated oncogenes MDM2 (25/35), MDM4 (2/35), and CDK6 (2/35). We further observed recurrent co-amplifications in PDGFRA (21/35), CDK4 (15/35), TERT (11/35), HDAC9 (9/35), and CCND1 (4/35). Sporadic co-amplifications occurred in MYC, MYCN, and MET (each 1/35). The tumor suppressor CDKN2A/B was frequently deleted (10/35). Interestingly, DNA methylation profiling (t-SNE) revealed an overlap of ISA and cardiac UPS. This “ISA” methylation signature was distinct from potential histologic and molecular mimics. In conclusion, our data reveal MDM4 and CDK6 amplifications in ISAs and UPS of the left atrium, lacking MDM2 amplification. We further report novel co-amplifications of various oncogenes, which may have therapeutic implications. Finally, the genetic and epigenetic concordance of ISAs and UPS of the left atrium further supports a shared pathogenesis and common classification.